The Prediction of a relationship between behavioural threshold, acoustic reflex threshold and loudness discomfort level - Sridhar. K. Murthy (Journal of All India Institute of Speech and Hearing, 1970)
The current study was carried out to explore and predict the relationship between three audiological measures viz. Behavioural Threshold Acoustic Reflex Threshold(ART) and Loudness Discomfort Level (LDL) in normal and sensorineural hearing impaired listeners.